2018
DOI: 10.1155/2018/1802671
|View full text |Cite
|
Sign up to set email alerts
|

Highway Project Value of Money Assessment under PPP Mode and Its Application

Abstract: The application of Public-Private Partnership (PPP) mode in transportation infrastructure construction has achieved more progress worldwide; now this mode has been adopted in highway projects of China from 2015. In the application of PPP mode, there are three main facts in China, which include whether the government is responsible for land acquisition and resettlement (LAR), the discount rate changes, and the replacement of business tax by value-added tax (VAT) in 2016. So this paper discusses Value for Money … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In terms of types of PPP project contacts to be adopted UNRA in the roads sector in Uganda, the findings revealed that a number of respondents interviewed disagreed with the statement that UNRA intends to adopt Public Finance Initiative PPP Project contact in the roads sector. Therefore, this finding of the study does not reflect the reviews of scholars such as Mehmet & Cuma (2018), Hu & Han (2018) and Kamau (2016) who contend that a Public Finance Initiative (PFI) is a type of PPP project contract where the public entity enters into a contractual arrangement with the private sector entity so that the private entity is authorized to provide services to the public through designing, building, financing and operation of a road facility.…”
Section: Types Of Ppp Project Contracts To Be Adopted By Unra In the mentioning
confidence: 64%
See 2 more Smart Citations
“…In terms of types of PPP project contacts to be adopted UNRA in the roads sector in Uganda, the findings revealed that a number of respondents interviewed disagreed with the statement that UNRA intends to adopt Public Finance Initiative PPP Project contact in the roads sector. Therefore, this finding of the study does not reflect the reviews of scholars such as Mehmet & Cuma (2018), Hu & Han (2018) and Kamau (2016) who contend that a Public Finance Initiative (PFI) is a type of PPP project contract where the public entity enters into a contractual arrangement with the private sector entity so that the private entity is authorized to provide services to the public through designing, building, financing and operation of a road facility.…”
Section: Types Of Ppp Project Contracts To Be Adopted By Unra In the mentioning
confidence: 64%
“…al., (2014), there are various PPP Project contract types used in the roads sector. The Private Finance Initiative (PFI) PPP project contract was first used by the UK government when it passed a legislation to use it in the construction of a number of highway infrastructure projects (Hu & Han, 2018). Mehmet and Cuma (2018) contend that a PFI is a type of PPP Project contract where the public entity enters into a contractual arrangement with the private sector entity so that the private entity is authorized to provide services to the public through designing, building, financing and operation of a road facility.…”
Section: Types Of Ppp Project Contractsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the PPP mode promotion intensity and the market acceptance degree of the utility tunnel are different due to different regions, which reflects the integration of different regions. The ability to use the PPP mode of the pipe gallery is somewhat helpless [42,43,44].…”
Section: Project Investment and Financing Structure And Risk Evaluationmentioning
confidence: 99%
“…There have been rapid increases over recent years in the use of public-private partnerships (PPPs) in place of traditional procurement. PPP has been utilised by governments around the world as an alternative approach to the traditional procurement methods (Khaderi et al, 2019;Palcic et al, 2019;O'Shea et al, 2018), due to the benefits gained from private sector participation such as alternative financing (Khaderi et al, 2019;Dewulf et al, 2012;The World Bank, 2017a), positive impact on quality and efficiency (Sadeghi et al, 2019;Ceruti, 2017;WBI, 2017), and providing value for money (Hu and Han, 2018;Yescombe and Farquharson, 2018;WBI, 2017).…”
Section: Introductionmentioning
confidence: 99%